Високоміцні бетони транспортного призначення з підвищеною довговічністю - Гуняк, Олексій Миколайович (Національний університет "Львівська політехніка", 2019)
Дисертаційна робота присвячена питанням підвищення довговічності високоміцних бетонів транспортного призначення шляхом системного поєднання пуцоланових полідисперсних компонентів, суперпластифікатора та повітровтягувальної добавки для покращення їх мікро- та мезоструктури. Встановлена багатофункціональна роль полідисперсного цеолітового компоненту, що полягає в оптимізації гранулометричного складу бетону на мезоструктурному рівні, формуванні щільної однорідної мікроструктури цементної матриці, а також в створенні внутрішнього резерву води для запобігання самообезводненню бетону. Розроблено та оптимізовано за критеріями міцності склади цементних бетонів для транспортного будівництва з використанням пористих пуцоланічних мінеральних компонентів та доведена їх ефективність у здійсненні функції внутрішнього догляду. Досліджено їх вплив на фізико-механічні властивості, тріщиностійкість та показники довговічності бетонів на основі сумішей різної рухливості. Проведено дослідно-промислове впровадження розроблених високоміцних бетонів транспортного призначення та обгрунтовано їх техніко-економічну ефективність. Диссертация посвящена вопросам повышения долговечности высокопрочных бетонов транспортного назначения путем системного сочетания пуццолановых полидисперсных компонентов, суперпластификатора и воздухововлекающей добавки для улучшения их микро- и мезоструктуры. Установлена многофункциональная роль полидисперсного цеолитового компонента, которая заключается в оптимизации гранулометрического состава бетона на мезоструктурном уровне, формировании плотной однородной микроструктуры цементной матрицы, а также в создании внутреннего резерва воды для предотвращения самообезвоживания бетона. Разработаны и оптимизированы по критериям прочности составы цементных бетонов для транспортного строительства с использованием пористых пуццоланических минеральных компонентов и доказана их эффективность в осуществлении функции внутреннего ухода. Исследовано их влияние на физико-механические свойства, трещиностойкость и показатели долговечности бетонов на основе смесей различной подвижности. Проведено опытно-промышленное внедрение разработанных высокопрочных бетонов транспортного назначения и обосновано их технико-экономическую эффективность. The thesis is devoted to the development of high-strength concrete with the enhanced durability for highway engineering. The incorporation of both pozzolanic polydisperse components and chemical admixtures of plasticizing and air-entraining action allows to obtain the improved meso- and microstructure of concrete. The role of particle size distribution, chemical composition and structure of zeolitic component in the realization of its properties as a porous pozzolanic mineral additive has been shown. It has been established that the polydisperse zeolitic component is characterized by higher activity in comparison with the polydisperse perlitic component as well as the pozzolanic activity coefficient of polydisperse mineral components exceeds fine-dispersed ones. The polydispersity of zeolitic component also provides the optimization of particle size distribution at the mesostructure level of concrete by compensating the absence of grains in the range of 60-160 μm. The formation of dense, fine-porous and fine-crystalline structure of cement paste has been confirmed. It is provided by the presence of fibrous needle-like calcium hydrosilicates CSH (I), which lead to colmatation of pores and reinforcement of contact zones. It has been proved that high strength of fine-grained concrete containing polydisperse zeolitic component is achieved due to its active role in the formation of both microstructure and mesostructure of the hardening system. Natural polydisperse porous mineral component with unique properties such as zeolitic tuff can be also used for incorporation of internal curing water with minor or without detrimental effect on the mechanical properties of high-strength concrete. It was found that the internal relative humidity of concrete with addition of polydisperse zeolitic component is 10% higher compared to the control concrete after 14 days of curing in dry conditions. The addition of polydisperse zeolitic component mitigates self-dessication of concrete and prolonges the hydration of cement. The mix proportions of concrete incorporating porous polydisperse mineral component and chemical admixtures for highway engineering have been designed and optimized. Such complex modification leads to 7-15% higher bending strength, better resistance to freeze-thaw cycles (F150), higher fracture energy (ΔGF = 67 J/m2) and lower carbonation depth (h=2 mm) of the optimized concrete composition. The addition of both zeolitic component and air-entraining agent results in 5,4 times lower shrinkage deformation of concrete. The water penetration depth of hardened concrete is 3,5 mm, therefore it can be attributed to waterproof. Total porosity and average pore diameter are reduced by 37 and 33% respectively for concrete with the addition of polydisperse zeolitic component. The combination of air-entraining agent together with polydisperse zeolitic component and superplasticizer results in optimal content and uniform distribution of fine air bubbles, which act as stress dampers, contributing to slow down both the process of microcrack formation in pre-peak stage (Gi=247 J/m2) and crack propagation in the postpeak stage (WL=295 J/m2). The pilot industrial application of the developed high-strength concrete for highway engineering was carried out constructing concrete pavement and manufacturing concrete interlocking blocks. The economic efficiency of the industrial application of high-strength concrete is UAH 92 000 per 1000 m2 of pavement. The estimated annual economic impact of reducing the manufacturing cost of concrete interlocking blocks is UAH 656 640.
Высокопрочные бетоны транспортного назначения с повышенной долговечностью
High-strength concrete with enhanced durability for highway engineering
Keywords: високоміцні бетони; полідисперсні пуцоланові компоненти; внутрішній догляд; довговічність бетонів транспортного призначення; будівельно-експлуатаційні властивості; высокопрочные бетоны; полидисперсные пуццолановые компоненты; внутренний уход; долговечность бетонов транспортного назначения; строительно-експлуатационные свойства; high-strength concrete; polydisperse pozzolanic components; internal curing; the durability of concrete for highway engineering; concrete structural properties; 691.328